Impacts of salinization caused by sea level rise on the biological processes of coastal soils - A review - Sadat Mazhar; Elisa Pellegrini; Marco Contin; Carlo Bravo; Maria De Nobili (Frontiers in Environmental Science, 2022)
Soil salinization caused by sea level rise threatens coastal agricultural soils and geochemically important wetlands worldwide. The aim of this review is to outline expected changes in soil biological activity by discussing the combined effects of salt stress and flooding on plants productivity and soil microbial communities, which determine consequences on fluxes of C, N and P. Finally, it outlines the expected repercussions on greenhouse gases emissions. The prediction of outcomes is made difficult by the concomitant and sometimes contrasting actions of flooding and seawater intrusion on partly acclimated and non-acclimated environments. Non-salt acclimated plants suffer from osmotic stress, but also from reduced O2 solubility. Microbial biomass declines with increasing salinity and microbial communities shift in composition. Large concentrations of Cl− inhibit nitrification, but salinity stimulates N2O fluxes. Impacts on C mineralisation rates is variable but enhanced by the larger availability of terminal electron acceptors. The reduction of Fe combined with that of SO42− could enhance P mobility. Salinization affects methanogenesis which is constrained in favour of SO42− reduction. Consequences are largely site specific and difficult to predict because of the complex network of processes occurring simultaneously in different compartments (i.e., soil, microbiome, vegetation). The distinction between short and long term effects is also important. A reliable prediction of outcomes at a planetary scale will only result from more precise inventories and monitoring of areas displaying specific similarities and from the implementation from these well-defined data sets of specifically devised models whose results can be finally combined on a weighted basis.